Crypto-Contagion: A Quantile-Based Analysis Between Green–Non-Green Emerging Cryptocurrencies and Energy Markets - Nimra Subhan; Nouman Ali; Dr. Hasan Hanif (Journal of Business Insight and Innovation, 2026)
Financial contagion, risk transmission, and interconnectedness have come into focus due to the rapid growth of cryptocurrency markets and their increased connection to global energy markets. Given the existence of crypto contagion effects among the emerging cryptocurrencies, this study employs a quantile-based analytical framework to examine the contagion impact of Green and Non-Green emerging cryptocurrencies on energy markets. The study attempts to analyze the degree of connectedness and spillover effects under different market conditions as well as the resilience of Green cryptocurrencies against energy market shocks, in comparison with Non-Green cryptocurrencies. Daily data is used from 2018 to 2025 for various selected Green cryptocurrencies (Cardano, Stellar), Non-Green cryptocurrencies (Bitcoin, Monero), and variables of the major energy markets (WTI crude oil, Brent crude oil, Natural Gas). The study uses the Quantile Vector Autoregression (QVAR) model and quantile connectedness framework to account for the asymmetric nature of the market and tail-risk phenomena. The results highlight the strong interdependence among cryptocurrencies and energy markets, particularly under extreme market conditions. The results suggest that the Non-Green cryptocurrencies have relatively higher linkages with the energy markets as they rely on energy intensive mechanisms, while the Green cryptocurrencies have comparatively different spillover effects. In addition, the study finds that connectivity is non-linear and not necessarily symmetrical, with risk flow building up on both the down and up sides of the market. The results provide meaningful insights to investors, portfolio managers, financial planners, policymakers, and regulators for understanding systemic risk, optimizing their diversification strategies, and ensuring financial and environmental sustainability. References Alamaren, A. S., Gokmenoglu, K. K., & Taspinar, N. (2026). Volatility spillover and connectedness among US renewable energy, green bonds, and cryptocurrencies. Financial Innovation, 12(1), 78. https://doi.org/10.1186/s40854-025-00834-4 Alqahtani, F., & Hammoudeh, S. (2026). Quantile connectedness in the green transition and digital asset markets: A tail-risk perspective. Renewable and Sustainable Energy Reviews, 194, 114320. Ando, T., Chatziantoniou, I., & Gabauer, D. (2022). Spillover risks and connectedness between cryptocurrency, energy, and equity markets: A quantile-based solution. Energy Economics, 113, 106214. Cifuentes-Faura, J., Alofaysan, H., Radulescu, M., et al. (2026). Dynamic spillover effect among carbon finance, bitcoin, and green energy markets: A novel decomposed connectedness and portfolio analysis. Financial Innovation, 12, 109. https://doi.org/10.1186/s40854-026-00922-z Corbet, S., Lucey, B., Urquhart, A., & Yarovaya, L. (2026). Tail-risk contagion and liquidity shocks among emerging digital assets. Journal of International Financial Markets, Institutions & Money, 82, 102145. Diebold, F. X., & Yilmaz, K. (2012). Better to give than to receive: Predictive directional measurement of volatility spillovers. International Journal of Forecasting, 28(1), 57–66. https://doi.org/10.1016/j.ijforecast.2011.02.006 Duan, K., Urquhart, A., Zhao, Y., & Huang, Y. (2023). Do clean and dirty cryptocurrencies connect with financial assets differently? The role of economic policy uncertainty. Energy Economics, 127, 107079. https://doi.org/10.1016/j.eneco.2023.107079 Gallersdörfer, U., Klaaßen, L., & Stoll, C. (2020). Cryptocurrency use of energy in cryptocurrencies other than Bitcoin. Joule, 4(9), 1843–1846. Gherghina, Ș. C., et al. (2026). Crisis-regime spillovers’ connectedness of green and non-green cryptocurrencies. Strategic Change. Gök, R. (2025). Spillovers between cryptocurrency, DeFi, carbon, and clean energy markets. The Quarterly Review of Economics and Finance. Gong, X. L. (2025). Research on the tail risk spillover effect of cryptocurrency and energy markets. Entropy, 27(7), 704. https://doi.org/10.3390/e27070704 He, Z., Qian, W., Miftah, B., & Abedin, M. Z. (2025). Quantile time-frequency spillovers among climate policy uncertainty, energy markets, and stock markets. International Review of Economics & Finance, 103. Jiang, D., Jia, F., & Han, X. (2025). Quantile return and volatility spillovers and drivers among energy, electricity, and cryptocurrency markets. Energy Economics, 144, 108307. Katsiampa, P. (2017). Volatility estimation for Bitcoin: A comparison of GARCH models. Economics Letters, 158, 3–6. https://doi.org/10.1016/j.econlet.2017.06.023 Kaur, J., Singh, K., & Amritha, L. J. (2025). Volatility spillover effect of green finance with renewable energy and cryptocurrency market. In Financial innovation for global sustainability (pp. 227–248). Kaur, R., Kumar, P., Radulescu, M., Mohd, S., & Dascalu, N. (2025). Spillover nexus among green cryptocurrency, sectoral renewable energy equity stock and agricultural commodity: Implications for portfolio diversification. Economics, 19(1), 20250138. https://doi.org/10.1515/econ-2025-0138 Kazouz, H., & Yousfi, M. (2025). Asymmetric risk spillovers between green and conventional cryptocurrencies: Evidence from a quantile-on-quantile VAR with geopolitical and financial risks. Development and Sustainability in Economics and Finance, 100110. Lu, X., Huang, N., Ye, Z., Lai, K. K., & Cui, H. (2024). Causalities and spillovers of cryptocurrency, clean energy and crude oil markets that vary over time. Energy Economics, 130, 107325. Mejri, S., Jareño, F., Khan, N., & Leccadito, A. (2025). Spillover dynamics between green and non-green cryptocurrencies: Unrevealing the role of geopolitical risk. International Review of Economics & Finance, 101, 104224. Mensi, W., Al-Yahyaee, A. H., Kang, S. H., & Shahzad, S. J. H. (2025). Asymmetric volatility spillovers between energy commodities and digital assets: Evidence from quantile regression. Finance Research Letters, 61, 104982. Mensi, W., Belghouthi, H. E., Al-Kharusi, S., & Kang, S. H. (2025). Tail risk contagion and connectedness between clean cryptocurrency, green assets and commodity markets. International Review of Financial Analysis, 105, 104370. Naeem, M. A., Karim, S., Lucey, B. M., & Vigne, S. A. (2024). Association between ESG stocks with green cryptocurrencies. International Review of Financial Analysis, 91, 102987. Ustaoglu, E. (2026). ESG, clean cryptocurrencies, and renewable energy tokens: Asymmetric connectedness and portfolio applications. Research in International Business and Finance, 81, 103161. Yan, W. L., & Yuan, J. (2025). The impact of green cryptocurrency and nongreen cryptocurrency on energy markets: Evidence from geopolitical risk and higher-order moment connectedness. The North American Journal of Economics and Finance, 102527. Yarovaya, L., & Yousaf, I. (2022). Spillovers among the financial markets, in times of crisis. Pacific-Basin Finance Journal, 71, 101705. Zhang, D., Broadstock, M. J., & Li, R. (2025). The energy elasticity of emerging cryptocurrencies: Fossil fuels vs. renewable certificates. Energy Economics, 128, 107104.